Microinfusion of a Corticotrophin-Releasing Hormone Receptor 1 Antisense Oligodeoxynucleotide into the Dorsal Hippocampus Attenuates Stress Responses at Specific Times After Stress Exposure - Kozlovsky, N.; Zohar, J.; Kaplan, Z.; Cohen, H. (Journal of neuroendocrinology, 2012)
Corticotrophin‐releasing hormone (CRH) plays a key role in the adjustment of neuroendocrine and behavioural adaptations to stress. Dysregulation in CRH systems has been implicated in a variety of stress‐related psychiatric disorders such as post‐traumatic stress disorder (PTSD). The present study examined the relationship between stress‐induced PTSD‐like behavioural response patterns and levels of CRH, CRH receptor (CHR‐R)1 and phosphorylated extracellular signal‐regulated kinase (pERK1/2) in the rat hippocampus subregions. The effects of pharmacological manipulations on behavioural, physiological and response patterns of brain‐derived neurotrophic factor (BDNF) and pERK1/2 expression using a CRH receptor (CRH‐R)1‐antisense oligodeoxynucleotide (CRH‐R1‐ASODN) were evaluated. CRH and CRH‐R1 mRNA and pERK1/2 protein levels were assessed in the hippocampus subregions 7 days after exposure to predator scent stress (PSS). The effects of CRH‐ASODN versus CRH‐Scrambled‐ODN microinfusion to the dorsal hippocampus either 1 h or 48 h post‐exposure on behavioural tests (elevated plus maze and acoustic startle response) were evaluated 7 days later, 14 days after PSS exposure. Localised brain expression of BDNF and ERK1/2 was subsequently assessed. All data were analysed in relation to individual behaviour patterns. A distinct pattern associated with extreme behavioural response (EBR) was revealed in the bioassay of behavioural study subjects, classified according to their individual patterns of behavioural response at 7 days. These EBR individuals displayed significantly higher CRH and CRH‐R1 mRNA levels in the CA1 and CA3 areas, mediating down‐regulation of pERK1/2 protein levels. Microinfusion of a CRH‐R1‐ASODN into the dorsal hippocampus 48 h after stress exposure, although not immediately after exposure (1 h), significantly reduced behavioural disruption and was associated with concomitant up‐regulation of BDNF and pERK1/2 protein levels compared to CRH‐R1‐Scrambled ‐ODN controls. CRH/CRH‐R1 is actively involved in the neurobiological response to predator scent stress processes and thus warrants further study as a potential therapeutic avenue for the treatment of anxiety‐related disorders.